2022
DOI: 10.1093/jn/nxac198
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Inequities in Food, Energy, Protein, Fat, and Carbohydrate Intakes in Rural Bangladesh

Abstract: Background Tracking dietary changes can inform strategies to improve nutrition, yet there is limited evidence on food consumption patterns and how disparities in food and nutrient intakes have changed in Bangladesh. Objectives We assessed trends and adequacies in energy and macronutrient intakes and evaluated changes in inequities by age group, sex, and expenditure quintile. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…This again potentially indicates that, while many people may have consumed meals from those categories, the quantity ingested was most likely insufficient, as previously noted by Arsenault et al [ 8 ]. Interestingly, the estimated values of calories and protein consumption from the sample of the present study appear to be lower than the reported values for women aged 19–40 in the 2018 Bangladesh Integrated Household Survey (BIHS) [ 32 ]. This suggests that the COVID-19 pandemic affected the WRA’s total food intake in Bangladesh, increasing their risk of nutritional deficiency, irrespective of the number of food groups consumed.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This again potentially indicates that, while many people may have consumed meals from those categories, the quantity ingested was most likely insufficient, as previously noted by Arsenault et al [ 8 ]. Interestingly, the estimated values of calories and protein consumption from the sample of the present study appear to be lower than the reported values for women aged 19–40 in the 2018 Bangladesh Integrated Household Survey (BIHS) [ 32 ]. This suggests that the COVID-19 pandemic affected the WRA’s total food intake in Bangladesh, increasing their risk of nutritional deficiency, irrespective of the number of food groups consumed.…”
Section: Discussioncontrasting
confidence: 87%
“…The present study demonstrated inadequate NARs for vitamin A, pyridoxine, folate, and iron among women irrespective of their dietary diversity situation. An analysis of the 2018 Bangladesh Integrated Household Survey (BIHS) panel data on food consumption revealed that despite the addition of legumes, eggs, milk, and dairy products to people’s diets, the quantity consumed accounted for just about a third of the amount, and meat intake remains less than half of the requirement, although rice intake exceeds the necessary level [ 32 ]. This again potentially indicates that, while many people may have consumed meals from those categories, the quantity ingested was most likely insufficient, as previously noted by Arsenault et al [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in four LMICs, Guatemala, India, Pakistan, and Congo also showed inadequately diversified dietary intake among pregnant women (Lander et al., 2019 ). However, evidence in Bangladesh showed that although dietary diversity has been improved in the last decade irrespective of age and sex, diets remain imbalanced with almost 70% energy come from carbohydrate (Ahmed et al., 2022 ). Literature suggests that in LMICs, several issues including low production (Harris‐Fry et al., 2015 ), poverty and food insecurity (Arimond, Wiesmann, Becquey, Daniels, et al., 2010 ; Brinkman et al., 2010 ; Harris‐Fry et al., 2015 ), and lack of nutritional knowledge contributed to inadequate dietary diversity and dependence to cereal‐based diets.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate meals and nutrient intakes are essential determinants of health, well-being, and survival [3]. The UNICEF conceptual framework highlights the influential position of age-appropriate, nutrient-wealthy meals on maternal and baby vitamins.…”
Section: Nutritient Intakementioning
confidence: 99%